Masjid design: Sources from revelation and traditions - Mohd Nawawi, Norwina; Nik Mohd Yusof, Nik Amirul Faiz (MPH Group Printing (M) Sdn Bhd, 2016)
This chapter attempts to give a review of the basis and the fundamentals of masjid design and building as extracted from the sources of revelation, the Qur’an and and the traditions of the Prophet (pbuh).